The association between atrial fibrillation and cognitive function in patients with heart failure. (February 2017) - Yang, Huifeng; Niu, Weihua; Zang, Xiaoying; Lin, Mei; Zhao, Yue
Background: Atrial fibrillation (AF) is associated with cognitive impairment in heart failure (HF). Aims: The purpose of this study was to examine whether AF independently predicted cognitive function in HF patients after controlling for more demographic, medical and psychological characteristics, and whether the timing of AF onset in relation to HF diagnosis independently contributed to cognitive function in HF patients with AF. Methods: A total of 188 hospitalized HF patients (62.8% male, age 66.3±10.6 years) completed cognitive function assessment with the Montreal Cognitive Assessment (MoCA). A history of AF, along with other medical characteristics, was ascertained through a review of participants' medical charts. The timing of AF onset in relation to HF diagnosis was categorized into AF occurring prior to HF diagnosis (i.e. prior AF) and AF developing after HF diagnosis (i.e. incident AF). Results: Altogether 72 participants had a positive diagnostic history of AF. Specifically, 41 had prior AF, and 31 developed AF subsequently. In HF patients, AF was associated with poorer performance on cognitive function after controlling for more confounders (β=−0.112, ΔR 2 = 0.010, p= 0.046). Among HF patients with AF, incident AF independently predicted poorer cognitive function (β=−0.238, ΔR 2 = 0.027, p= 0.047). Conclusion: AF independently contributes to cognitive function in HF patients after adjusting for more confounding variables. The timing of AF onset in relation to HF diagnosis independently predicts cognitive function in HF patients with AF. Prospective studies are needed to elucidate possible mechanisms for the association between AF and cognitive function in HF populations.